2014
DOI: 10.1159/000362262
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Augments Angiogenic Responses in a Neonatal Rat Model of Cerebral Unilateral Hypoxia-Ischemia

Abstract: Background: Recombinant human erythropoietin (rh-EPO) has been used as a drug to treat premature infant anemia for over a decade. In addition to its erythropoietic effect, rh-EPO has also been reported to have protective effects against brain injury. Objectives: Our aim was to evaluate the levels of angiogenesis-related cells (CD34+ cells) and angiogenic factors (vascular endothelial growth factor, VEGF, and angiopoietin-1, Ang-1) in a neonatal rat model of cerebral unilateral hypoxia-ischemia (HI) and to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
12
0
3
Order By: Relevance
“…Study suggests that CD34 is a marker of mononuclear cells that maintain vascular integrity by producing endothelial progenitor cells [21]. Consistent with the spike of CD34 + cells in HI-induced PWMD that was previously published by our group [30], vessel-lumen structures were detected 4 days after HI. We observed that the CD34 + cells first appeared as single cells and then accumulated cell-cell contacts.…”
Section: Discussionsupporting
confidence: 87%
“…Study suggests that CD34 is a marker of mononuclear cells that maintain vascular integrity by producing endothelial progenitor cells [21]. Consistent with the spike of CD34 + cells in HI-induced PWMD that was previously published by our group [30], vessel-lumen structures were detected 4 days after HI. We observed that the CD34 + cells first appeared as single cells and then accumulated cell-cell contacts.…”
Section: Discussionsupporting
confidence: 87%
“…[1] Brain damage of prematurity is the predominant form of the acquired brain damage in neonates who undergo neurological morbidity. [2] There are only limited therapies to improve the outcome from the HIBD. [3] Administration of the recombinant human-erythropoietin (rh-EPO) into extremely preterm infants at Neonatal Intensive Care Unit improved neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The present study therefore used an animal model to investigate the role of rh-EPO in enhanced neurological recovery, which was thought to be related to the promotion of angiogenesis. [25]…”
Section: Introductionmentioning
confidence: 99%
“…As described in our previous study [28], postnatal day 3 (P3) rats underwent permanent ligation of the right common carotid artery after anesthetization with ether. Pups were returned to the home cage for 2 h, then exposed to hypoxia (94% N2 + 6% O2) for 2h by being placed in a sealed chamber partially submersed in a 37°C water bath.…”
Section: Neonatal Rat Model Of Periventricular White Matter Damagementioning
confidence: 99%